Freedom of artistic and cultural expression: a critical analysis of the need for education in the face of censorship and trivialization of public space - Caeiro-Rodríguez, Martín (Arte, Individuo y Sociedad, 2026)
Whenever there is talk of freedom of expression, the debates are always situated in the legal-legislative sphere and in the margins of individual or collective freedom, in the limits of the right of others not to be insulted, in the affronts to one’s own honor or in what the law should allow to be done or said, indicating what is right or wrong or legal or illegal. But in the context of artistic and cultural education, the debate is quite different: freedom of artistic and cultural expression and its education is aimed at amplifying the minds and lives of children, adolescents and adults, to increase their expressive capacities and the exercise of a critical view and thinking and responsible communication. We analyze from a critical review the space in which freedom of expression occurs through various sources and authors, related terminology and identify problems and opportunities beyond censorship. We conclude with the need to educate in artistic and cultural expression from childhood for a society committed to the use of its artistic and cultural rights and freedoms in the public space.